Optimization of the Steering System to Improve the Maneuverability of the Barombong Training Ship - Sidrotul Muntaha; Rina Haryani; Mulyono Mulyono; Muhammad Yusuf (International Journal Labs, 2025)
The operation of the steering system on a training ship often faces technical and operational obstacles that affect the vessel's maneuverability and navigational safety. This study aims to determine the impact of maneuvering risks that hinder the operation of the steering system on the Barombong Training Ship, as well as efforts for optimization of the steering system to improve the maneuverability of the Barombong Training Ship and navigational safety. The method used is descriptive qualitative, with an in-depth analysis of empirical data obtained from interviews, observations, and documentation on the Barombong Shipping Polytechnic Training Ship. The data were analyzed using the USG (Urgency, Seriousness, Growth) method to determine problem priorities. The results of the study show that the ship’s steering system is vital for ensuring navigational safety and maneuverability. Routine inspection and maintenance of the steering system—including checks on hydraulic pressure, rudder components, steering gear, and hydraulic fluid—are essential to prevent system failures. Additionally, ship maneuvers must be conducted carefully, with proper adjustments to the vessel’s speed based on sea and weather conditions to avoid excessive strain on the steering system. Effective communication among crew members and maneuvering drills under varying conditions are also critical for responding to emergency situations. Proper load distribution and speed reduction under certain conditions further enhance steering performance. This study recommends regular inspections, adequate maintenance, and consistent training to improve crew competence in maintaining the operational safety and maneuverability of the Barombong Training Ship.